Рredicting epizootic risks of leptospirosis - Kozishkurt, E.; Talalaev, K.; Melnik, O.; Sovirda, O.; Gerasimenko, E.; Kostolonova, L. (Journal of Education, Health and Sport, 2022)
Leptospirosis is an infectious disease of humans and animals that is caused by pathogenic spirochetes of the genus Leptospira. It is considered the most common zoonosis in the world and is associated with settings of poor sanitation and agricultural occupations involving contact with animals or water. The authors have analyzed the present day world and particular Ukrainian situation with leptospirorsis and pointed out the urgent measures which could prevent its prevalence.